2019
DOI: 10.12659/msm.918841
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Hyperuricemia with Lipid Storage Myopathy: A Clinical Study

Abstract: Background: In this study, we investigated the clinical and pathological features of patients with lipid storage myopathy (LSM) complicated with hyperuricemia, to improve clinicians' understanding of metabolic multi-muscular disorder with metabolic disorders, and to reduce the risk of missed diagnosis of LSM. Material/Methods: From January 2005 to December 2017, 8 patients underwent muscle biopsy and diagnosed by muscle pathology and genetic testing in our hospital. All 8 patients were in compliance with LSM d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
1
Order By: Relevance
“…Drug-induced myopathy is characterized by acute symptoms such as myogenic damage, muscle pain, and elevated CK levels in patients without preexisting muscle conditions, who have been exposed to therapeutic doses of certain drugs. 6,8 The diverse causes of drug-induced myopathy lead to clinical or biochemical signs of muscle involvement, typically improving upon discontinuation of the suspected drug; thus, confirming the diagnosis of drug-induced myopathy. However, despite understanding the causative factors, predicting the occurrence of drug-induced myopathy in clinical practice remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced myopathy is characterized by acute symptoms such as myogenic damage, muscle pain, and elevated CK levels in patients without preexisting muscle conditions, who have been exposed to therapeutic doses of certain drugs. 6,8 The diverse causes of drug-induced myopathy lead to clinical or biochemical signs of muscle involvement, typically improving upon discontinuation of the suspected drug; thus, confirming the diagnosis of drug-induced myopathy. However, despite understanding the causative factors, predicting the occurrence of drug-induced myopathy in clinical practice remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the patient was diagnosed with hyperuricemia in the first hospital, but his uric acid decreased gradually after taking riboflavin without using a uric acid-lowering drug. A study involving eight patients with LSM complicated by hyperuricemia found that men with LSM are more likely to develop hyperuricemia than women with LSM because of the benefit of estrogen ( 8 ). The cause of hyperuricemia is mainly related to decreased uric acid excretion, which could be explained by renal tubular disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, long-term high serum uric acid (SUA) may cause many complications. Current studies have shown that 1) anomalous high SUA level is likely to induce a series of cardiovascular diseases, and acts as an independent risk factor for cardiovascular diseases, including atherosclerosis, hypertension, and coronary heart disease (Edwards, 2009); 2) obesity can cause hyperuricaemia, further leading to lipid metabolism disorder and chronic diseases (Fernandes Silva et al, 2019;Jingzhe Han et al, 2019); 3) in patients with diabetes, high uric acid (UA) further damages pancreatic cells and worsens diabetic condition (Changgui Li and Chang, 2013;Yun-Hong Lu et al, 2020). In summary, hyperuricaemia has become a key risk factor for development of many serious diseases.…”
Section: Introductionmentioning
confidence: 99%